2018
DOI: 10.1002/ece3.4389
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic genetic variation and adaptation to waterlogging in Caledonian Scots pine, Pinus sylvestris L.

Abstract: Local adaptation occurs as the result of differential selection among populations. Observations made under common environmental conditions may reveal phenotypic differences between populations with an underlying genetic basis; however, exposure to a contrasting novel environment can trigger release of otherwise unobservable (cryptic) genetic variation. We conducted a waterlogging experiment on a common garden trial of Scots pine, Pinus sylvestris (L.), saplings originating from across a steep rainfall gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…However, between the most eastern and most western populations, there is a lag of over 2 weeks in peak pollen production, which would limit gene flow between the geographic extremes (Whittet et al, 2017). Local adaptation has been demonstrated in these populations along the west-to-east gradient for a number of traits, including needle morphology (Donnelly et al, 2016), response to waterlogging (Donnelly et al, 2018), photochemical capacity (Salmela et al, 2011), and spring phenology (Salmela et al, 2013). Because mycorrhizal fungal communities in this pinewood system have also been shown to vary longitudinally along a rainfall gradient (Jarvis et al, 2013), we believe that the absence of local adaptation we found is due to a lack of selection for mycorrhizal response rather than the homogenizing effects of gene flow.…”
Section: Local Adaptationmentioning
confidence: 99%
“…However, between the most eastern and most western populations, there is a lag of over 2 weeks in peak pollen production, which would limit gene flow between the geographic extremes (Whittet et al, 2017). Local adaptation has been demonstrated in these populations along the west-to-east gradient for a number of traits, including needle morphology (Donnelly et al, 2016), response to waterlogging (Donnelly et al, 2018), photochemical capacity (Salmela et al, 2011), and spring phenology (Salmela et al, 2013). Because mycorrhizal fungal communities in this pinewood system have also been shown to vary longitudinally along a rainfall gradient (Jarvis et al, 2013), we believe that the absence of local adaptation we found is due to a lack of selection for mycorrhizal response rather than the homogenizing effects of gene flow.…”
Section: Local Adaptationmentioning
confidence: 99%
“…While individual publications show evidence of CGV (Badyaev, 2005;Donnelly et al, 2018;Ledón-Rettig et al, 2009McGuigan et al, 2011;Rohner et al, 2013;Rutherford & Lindquist, 1998), evidence synthesis is equivocal (Noble et al, 2019;Rowiński & Rogell, 2017;Wood & Brodie, 2015. Here, we conducted a meta-analysis using systematic criteria for defining novel environments to answer two questions: (1) Does total additive genetic variation increase in novel environments versus ancestral environments?…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the hidden reaction norms of different genotypes express 'cryptic genetic variation' (Figure 15.1). Such cryptic genetic variation has been suggested to represent a store of variability that can be revealed in novel environments or genetic backgrounds Moczek 2008;Donnelly et al 2018;Zheng et al 2019;Pilakouta et al 2020). Zan and Carlborg (2020) investigated the organization of 130 yeast growth regulation genes in response to 20 different growth media.…”
Section: The Context-dependence Of Gene Expressionmentioning
confidence: 99%